2004
DOI: 10.1074/jbc.m312735200
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix-induced Cyclooxygenase-2 Regulates Macrophage Proteinase Expression

Abstract: Chronic inflammatory diseases are characterized by the persistent presence of macrophages and other mononuclear cells, tissue destruction, cell proliferation, and the deposition of extracellular matrix (ECM). The tissue degradation is mediated, in part, by enhanced proteinase expression by macrophages. It has been demonstrated recently that macrophage proteinase expression can be stimulated or inhibited by purified ECM components. However, in an intact ECM the biologically active domains of matrix components m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 65 publications
4
56
0
Order By: Relevance
“…MMP-9 expression is low or absent in most normal tissues, but is markedly upregulated during chronic inflammation and cancer (Parks et al, 2004). MMP-9 expression was markedly reduced in macrophages isolated from COX-2-deficient mice and in wild-type macrophages treated with COX-2 inhibitors (Khan et al, 2004). Consistent with these results, pharmacological EP4 activation increased MMP-9 expression and activity in human monocytes and macrophages derived from atherosclerotic plaque (Cipollone et al, 2005).…”
supporting
confidence: 76%
“…MMP-9 expression is low or absent in most normal tissues, but is markedly upregulated during chronic inflammation and cancer (Parks et al, 2004). MMP-9 expression was markedly reduced in macrophages isolated from COX-2-deficient mice and in wild-type macrophages treated with COX-2 inhibitors (Khan et al, 2004). Consistent with these results, pharmacological EP4 activation increased MMP-9 expression and activity in human monocytes and macrophages derived from atherosclerotic plaque (Cipollone et al, 2005).…”
supporting
confidence: 76%
“…We have recently shown that MMP-9 mediates the transmigration of activated neutrophils across fibronectin (29), a key ECM protein expressed very early by endothelial cells in liver I/R injury (31). Others have shown that COX-2 inhibition in vitro is able to block ECM-induced MMP-9 by RAW264.7 macrophage-like cells (55), likely by targeting PGE 2 receptors in these cells (56). In our study, COX-2 Ϫ/Ϫ mice had reduced numbers of MMP-9-positive neutrophils infiltrating the livers after I/R injury; thus, it is reasonable to postulate that COX-2, through selective prostanoid-receptor interactions, may also regulate MMP-9 expression by these cells.…”
Section: Discussionmentioning
confidence: 99%
“…28 MMPs-1, -2, -3, -7, -9, -10, -12, -14, and -19 appear to be coordinately upregulated in HPBM or monocyte cell lines after brief culture on or adhesion to preformed ECM 29 or defined ECM components including laminin, collagen, SIKVAV peptide, fibronectin or extracellular MMP inducer (EMMPRIN) 28,30 -37 (supplemental Table I, available online at http://atvb.ahajournals.org). Binding to platelets enhances the effects of binding to ECM proteins, owing to cooperation between signaling from integrins and P-selectin.…”
Section: Peripheral Blood Monocytes and Monocyte Cell Linesmentioning
confidence: 99%
“…29,33 MMP upregulation can be mimicked by adding PGE2 39,40 or forskolin, 41 a direct activator of adenylate cyclase. Induction of MMPs may be blocked by integrin-blocking antibodies 36 and by COX inhibitors, including selective COX-2 inhibitors, 29,33,40 and antagonists at the EP4 receptor.…”
Section: Peripheral Blood Monocytes and Monocyte Cell Linesmentioning
confidence: 99%